Emerging insights into thyroid cancer from immunotherapy perspective: A bibliometric analysis - Qianyu Wang; Gang Pan; Yu Zhang; Yiqin Ni; Yuzhu Mu; Dingcun Luo (Taylor & Francis Group, 2024)
Thyroid cancer is a common endocrine malignancy that poses considerable therapeutic challenges in treating anaplastic carcinoma and advanced aggressive disease. Immunotherapy has become a prominent strategy for cancer treatment, and has shown remarkable advancements in recent years. In this study, we utilized visualization and bibliometric tools to analyze publications on thyroid cancer immunotherapy from the Web of Science Core Collection (WoSCC). A total of 409 articles were included, with an annual increase in both publications and citations since 2016. China leads research efforts in this area, while the University of Texas System and UTMD Anderson Cancer Center rank first in publication output. The journal Thyroid has garnered the highest citations. Notable authors contributing to this field include Antonelli Alessandro, Fallahi Poupak, and Wang Yu. Current research hotspots include immune checkpoint inhibitors, combination therapies involving immunotherapy with targeted therapy, CAR-T cell therapy, and modulation of the tumor microenvironment, all of which underscore the evolving landscape and potential for innovative treatments in thyroid cancer.